EU Citizens and Homelessness - Taylor, Owen (2021)
This chapter provides a description of the implementation of the European citizens’ survey, led by the French team from Aix Marseille University, as part of the HOME_EU project. The French team set out to use a telephone survey and quantitative research methods to investigate the opinions and experiences of European citizens in relation to homelessness, in addition to use a contingent valuation method to elicit the value respondents placed on the Housing First model as a potential solution to long-term homelessness. Data collection covered a 10-month period (March to December 2017). The survey produced results for European citizen’s knowledge, attitudes and practices (KAP) in relation to homelessness, willingness to pay (WTP) for the Housing First model, and the prevalence of homelessness among the ‘survey and the WP2 as a whole close the chapter.